1990
DOI: 10.1002/kin.550221007
|View full text |Cite
|
Sign up to set email alerts
|

A study of the reactions of NO3 radicals with organic sulfides: Reactivity trend at 298 K

Abstract: A laser flash photolysis-long path laser absorption technique has been employed to investigate the kinetics of NO3 reactions with CH3SCH3(kl), CDsSCD3(kz), and CzH5SCzHS(k3) in 500 torr air at 298 K. The dependence of k l on total pressure (20-500 torr) and oxygen partial pressure (0-100 torr) has also been investigated, with no dependence observed. Measured rate coefficients in units of cm3 molecule-' s-' are kl = 13 2 3, k p = 3.4 2 0.8, and k3 = 48 2 12, where the quoted uncertainties are %estimates of abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
26
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 40 publications
6
26
0
Order By: Relevance
“…As shown in Figure 11, pathway (a) gives the best prediction among the three, and pathway (a) is also consistent with all the available experimental evidence regarding the CH,SCH, + NO, reaction (see Part I for details). Furthermore, pathway (a) is supported by the very recent experimental evidence that the reaction of CH,SCH, with NO, does involve breaking a carbon-hydrogen bond (Daykin and Wine, 1990). The major difference between pathway (a) and pathways (b) and (c) is that NO, is regenerated from pathways (b) and (c), thus leading to a cycle in which CH,SCH, is consumed by NO,.…”
Section: Competition Between Adduct Decomposition and Bimolecular Reasupporting
confidence: 51%
See 1 more Smart Citation
“…As shown in Figure 11, pathway (a) gives the best prediction among the three, and pathway (a) is also consistent with all the available experimental evidence regarding the CH,SCH, + NO, reaction (see Part I for details). Furthermore, pathway (a) is supported by the very recent experimental evidence that the reaction of CH,SCH, with NO, does involve breaking a carbon-hydrogen bond (Daykin and Wine, 1990). The major difference between pathway (a) and pathways (b) and (c) is that NO, is regenerated from pathways (b) and (c), thus leading to a cycle in which CH,SCH, is consumed by NO,.…”
Section: Competition Between Adduct Decomposition and Bimolecular Reasupporting
confidence: 51%
“…Notice that the overall reaction of NO, addition followed by pathway (a) is the same as the direct H-atom abstraction for CH,SCH, + NO,. Regarding the possible reactions of the adduct with 0, and NO,, they may be too slow to compete with reaction pathway (a) since the apparent rate constant of CH,SCH, + NO,, recently observed by Daykin and Wine (1990), is found to be the same at 500 Torr air as at 19-500 Torr N,.…”
Section: Competition Between Adduct Decomposition and Bimolecular Reamentioning
confidence: 99%
“…The large isotope effect observed in this study has been confirmed by another group (Daykin et al, 1990), who found the same value of kH/k D. The hypothesis of a hydrogen abstraction by the nitrate radical is further supported by the observation of a large and fast build-up of nitric acid in the experiment as previously reported (Jensen et al, 1991), by the observation of deuterated nitric acid (DNO3) in the CD3SCD3 + NO3 experiment and finally by the fact that dimethylsulphoxide was not observed at any time in the experiments. The i.r.-spectrum of an intermediate of the reaction between NO3 + CH3SCH3, detectable only after a few seconds reaction time, is shown in Fig.…”
supporting
confidence: 78%
“…For this reason it seems likely, that the reaction initiates with the formation of an initial adduct and in a subsequent reaction step proceeds via Reaction 1 (a hydrogen abstraction) or Reaction 2 (an addition reaction producing dimethylsulphoxide) or Reaction 3 (an addition-decomposition reaction). All of these reactions have been considered in previous studies (Atkinson et al, 1984;Platt et al, 1990;Daykin et al, 1990;Jensen et al, 1991).…”
mentioning
confidence: 99%
“…The dominance of the isomerization process entails consequences for the OH budget and the subsequent product formation. The simulations reveal that the isomerization process increases the total OH radical formation rate by 2% on average and by 17% during nighttime when CH 3 SCH 2 O 2 formation via NO 3 + DMS 7,45 is active (see Figure S8). Furthermore, MSA formation from consecutive reactions of HOOCH 2 SCHO is impossible because no methyl group is left in this molecule.…”
Section: Dmsmentioning
confidence: 99%